Atrial fibrillation epidemiology, disparity and healthcare contacts: a population-wide study of 5.6 million individuals - Sheng-Chia Chung; Reecha Sofat; Dionisio Acosta-Mena; Julie A Taylor; Pier D Lambiase; Juan P Casas; Rui Providencia (Elsevier, 2021)
Background: We aimed to evaluate atrial fibrillation occurrence, reasons for healthcare visits, mortality, causes of death and examined patterns by relative deprivation in the UK.Methods: To study the atrial fibrillation (AF) incidence, mortality and case-fatality, we implemented a prospective cohort study with the linked electronic health records of 5.6 million population in the United Kingdom Clinical Practice Research Datalink from 1998 to 2016. A matched case-control study was used to investigate causes of hospitalisation and death comparing individuals with and without incident AF.Results: During a median follow-up of 10.3 years, 199,433(3.6%) patients developed incident AF. Increased risk of hospitalisation for heart failure, cardiovascular conditions and infection was present among patients who later developed AF. Following an AF diagnosis, patients were frequently admitted to the hospital for heart failure, lower respiratory tract infection, chronic obstructive pulmonary disease and ischemic heart disease. One in 5 AF patients died during the first year after diagnosis, and the mortality increased to 42.7% at the fifth year. The excess deaths in AF cases compared to controls may result from cardiovascular diseases, infection and metabolic disorders. Individuals from areas with higher deprivation in socioeconomic and living status had both higher AF incidence and fatality.Interpretation: We observed an elevated risk of hospitalisation for cardiovascular or respiratory diseases among incident AF patients, and the considerable disparity in AF burden by socioeconomic deprivation informs priorities for prevention and provision of patient care.Funding: The study was supported by the GlaxoSmithKline, University College London Hospital and National Institute for Health Research. The funders did not have any role in study design, data collection, data analysis, interpretation, and writing of the report.